2012
DOI: 10.4209/aaqr.2011.04.0045
|View full text |Cite
|
Sign up to set email alerts
|

Potential Source Analysis for PM10 and PM2.5 in Autumn in a Northern City in China

Abstract: In this study, PM 10 and PM 2.5 samples were obtained in a northern city in China. The 12-h averaged concentrations of particulate matter and species were analyzed. A PCA-MLR model was applied to identify the potential source categories and to estimate the source contributions for the PM 10 and PM 2.5 datasets. Five factors were extracted for the PM 10 samples, and their percentage contributions were estimated as follows: crustal dust-39.87%; vehicle exhaust-30.16%; secondary sulfate and nitrate-14.42%; metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…The highest average PM 10 concentration was obtained in urban areas like Agra, India (ranged from 270-290 μg/m 3 (Pipal et al, 2011) and Guangzhou, China (ranged from 120-130 μg/m 3 ) (Cao et al, 2004). The highest average PM 2.5 concentration was also obtained in urban areas like Agra, India (ranged from 80-90 μg/m 3 ) (Pipal et al, 2011) and Guangzhou, China (78 μg/m 3 ) (Cao et al 2004) and Ordos, China (51 μg/m 3 ) (Wang et al, 2012). The PM 10 , PM 2.5 and PM 0.1 concentrations obtained in this study were found to be the lowest in the Asian region, with mean values of about 39.45 ± 11.58, 21.82 ± 7.50 and 1.42 ± 0.56 μg/m 3 , respectively.…”
Section: Comparison Of Particle Concentrations and Source Contributiomentioning
confidence: 82%
See 1 more Smart Citation
“…The highest average PM 10 concentration was obtained in urban areas like Agra, India (ranged from 270-290 μg/m 3 (Pipal et al, 2011) and Guangzhou, China (ranged from 120-130 μg/m 3 ) (Cao et al, 2004). The highest average PM 2.5 concentration was also obtained in urban areas like Agra, India (ranged from 80-90 μg/m 3 ) (Pipal et al, 2011) and Guangzhou, China (78 μg/m 3 ) (Cao et al 2004) and Ordos, China (51 μg/m 3 ) (Wang et al, 2012). The PM 10 , PM 2.5 and PM 0.1 concentrations obtained in this study were found to be the lowest in the Asian region, with mean values of about 39.45 ± 11.58, 21.82 ± 7.50 and 1.42 ± 0.56 μg/m 3 , respectively.…”
Section: Comparison Of Particle Concentrations and Source Contributiomentioning
confidence: 82%
“…Several studies show that ambient particulate pollution is associated with certain health and environmental effects (Choosong et al, 2010;Ning et al, 2010;Wang et al, 2012). Trace elements are important components of aerosols, and industrial, residential, and traffic related activities have resulted in a substantial increase in trace metals (e.g., Cu, Pb, Zn, Cd, Ni etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The source can be associated with crustal dust. According to Wang et al(2012), dust is an important contributor to PM 2.5 , accounting for more than 25% of PM 2.5 mass concentration in urban areas. Soil resuspension is likely to be affected by Gobi or Thaklamakan dust events, which are known to influence particulate matter in Wuhan during 26 th May (Figs.…”
Section: Source Identification and Apportionment By Pmfmentioning
confidence: 99%
“…Thus, understanding the level of PM 10 and PM 2.5 (PM with an aerodynamic diameter less than 2.5 μm) in urban areas is important. Techniques such as source apportionment have been developed to control PM pollutants (Wang et al, 2012). Particulate trace metal concentrations are attributed to their distinguished unique emission sources.…”
Section: Introductionmentioning
confidence: 99%